PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN MEDIA INTERAKTIF ANIMASI TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPA KELAS V SD SWASTA FREE METHODIST 2 MEDAN - Finis Kristin Maduwu; Nova Florentina Ambarwati; Dyan Wulan Sari, H.S; Patri Janson Silaban; Rumiris Lumban Gaol (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to 1.) Find out whether using animated interactive media can improve student learning outcomes in science learning class VA at Free Methodist 2 Medan Private Elementary School. 2.) Know how learning is implemented after using the Discovery Learning learning model assisted by Animation Interactive Media in science lessons in the VA class of Free Methodist 2 Medan Private Elementary School. 3.) Find out whether there is an influence of animated interactive media on student learning outcomes in science learning class VA at Free Methodist 2 Medan Private Elementary School. This research method is quantitative research. The design of this research uses posttest and pretest experiments, with a sample of VA class research totaling 25 students. Data collection techniques in the study used observation, questionnaires, tests and documentation. Data analysis techniques used Correlation Coefficient Test and Hypothesis Test. There is an influence of the Discover Learning learning model on student learning outcomes in science lessons in class VA of Free Methodist 2 Medan Private Elementary School in the 2023/2024 Academic Year. It can be seen from the average pretest score of students of 47.52 and the average posttest score of students of 83.12. Based on the results of the hypothesis test (t-test) with a thieung value ≥ trabel, namely 6.620 ≥ 1.708 at a significance level of 0.000 <0.05. These data can show that Ha is accepted, namely there is an influence between the Discover Learning learning model (X) and student learning outcomes (Y).